Thaliporphine from Berberis lycium Royle - Syed Fazal Hussain (Baqai Journal of Health Sciences)
Chemical studies on the aerial part of Berberis lycium Royle belonging to the family Berberidaceae resulted in the isolation of the aporphine alkaloid ‘Thaliporphine’, the structure of which was elucidated by using spectroscopic techniques such as 1H NMR, 13C NMR, DEPT-90, DEPT-135 and Mass spectrometry. Although only nine aporphines have been isolated from different Berberis species, this is the first report of the isolation of thaliporphine from Berberis lycium.